The Influence of Health Education on Increasing Pregnant Women's Knowledge About the Benefits of Mch Books During Pregnancy at Jambi City Puskesmas - Olga Lolonda; Kamariyah Kamariyah; Muthia Mutmainnah; Indah Mawarti; Suryadi Imran (Westscience Press, 2025)
Public understanding in Indonesia about the benefits of MCH books is still low, so there is a lack of knowledge among mothers to recognize the signs and dangers of pregnancy due to low resources resulting in bleeding, malnutrition, hypertension, infection, rupture of membranes, lack of fetal movement and other complications suffered by mothers before pregnancy. One of the government's efforts to overcome this problem is by issuing a maternal and child health guidebook so that it can be read and other programs such as outreach related to KIA books. This study aims to determine the effect of health education on increasing pregnant women's knowledge about the benefits of KIA books during pregnancy at the Kenali Besar Community Health Center, Jambi City. This research uses a quantitative method with an experimental questionnaire approach with a one group pre test and post test design. The number of samples in this study was 30 and the population was 868 people. Respondents were taken using a purposive sampling technique. The statistical test used the Wilcoxon test. The results were obtained from the pre test. 16.63 and post test 26.76 results show a p-value of 0.000 (>0.05). Based on these results, it can be concluded that there is a significant influence between the provision of health education about the benefits of MCH books during pregnancy.